Intestinal Schistosomiasis as Unusual Aetiology for Acute Appendicitis, Nowadays a Rising Disease in Western Countries - I. López de Cenarruzabeitia; S. Landolfi; M. Armengol Carrasco (Case Reports in Infectious Diseases)
Intestinal schistosomiasis as unusual aetiology for acute appendicitis, nowadays a rising disease in western countries. Recent changes in global migration has led to an immigration growth in our scenario, upsurging people coming from endemic areas of schistosomiasis. Schistosomal appendicitis, seldom reported in developed countries, is now an expected incrising entity in our hospitals during the near future. Due to this circumstances, we believe that schistosomiasis should be consider as a rising source for acute appendicitis in western countries. In order to illustrate this point, we present a case of a 45-years-old black man, from Africa, was admitted via A&E because of acute abdominal pain, located in right lower quadrant. Acute appendicitis was suspected, and he underwent laparotomy and appendectomy. Pathological study by microscope revealed a gangrenous appendix with abscesses and parasitic ova into the submucosal layer of the appendix, suggesting Schistosomiasis.